Urban Leisure And Recreation Of The Igeneration In Denpasar, Bali - Juniawan, I Made (MSJ : Majority Science Journal, 2024)
Lifebalance has emerged as the solution to attaining happiness and well-being, counteracting the various modern ailments that afflict us. Humans, from the traditional era to the digital age, engage in a multitude of leisure and recreational activities with the aim of maintaining a balanced life. Nevertheless, the pervasive influence of technology and the internet has had a notable effect on human behaviors, particularly with the prevalence of 'phubbing'—a tendency to prioritize gadgets over interpersonal interactions and engagement with the surrounding environment. This phenomenon is particularly pronounced among the internet generation (iGeneration). This article delves into the socio-cultural changes in society related to leisure and recreation patterns, considering the backdrop of high interaction with information technology. The focus is on the meaning, significance, and extent to which Denpasar City serves as a hub for leisure and recreation. The study employs a qualitative approach, situated in the capital city of Denpasar, Bali. The research's primary subject is the iGeneration, spanning from 1995 to 2010 and currently aged between 13 and 28. Data collection methods include participatory observation, documentation, questionnaires, and structured interviews. The results indicate that the iGeneration's leisure and recreation patterns in Denpasar City encompass sports activities, social interactions, beach visits, shopping, and movie-watching. The interpretation of recreation can be classified into four distinct categories: as a means of physical and spiritual rejuvenation, as self-indulgence, as a platform for learning and skill development, and as an element of work-life balance. It's worth noting that around 56.6% of iGeneration recreation activities are centralized in Denpasar City, highlighting a preference for urban activities compared to those in rural areas or outside the city.